Refractive outcomes of phacoemulsification cataract surgery in glaucoma patients. Issue 3 (March 2018) - Manoharan, Niranjan; Patnaik, Jennifer L.; Bonnell, Levi N.; SooHoo, Jeffrey R.; Pantcheva, Mina B.; Kahook, Malik Y.; Wagner, Brandie D.; Lynch, Anne M.; Seibold, Leonard K.
Abstract : Purpose: : To evaluate refractive outcomes after phacoemulsification cataract surgery in patients with glaucoma. Setting: : University of Colorado Health Eye Center, Aurora, Colorado, USA. Design: : Retrospective case series. Methods: : The incidence of refractive surprise was evaluated in patients with and without glaucoma after phacoemulsification cataract surgery. Refractive surprise was defined as the difference in spherical equivalent of the refractive target and postoperative refraction in diopters (D). Results: : The study comprised 206 eyes in the glaucoma group and 1162 control eyes. The refractive surprise greater than ±0.5 D and ±1.0 D was 29.9% and 4.9% in the control group and 40.3% ( P = .0061) and 11.2% ( P = .0011) in the glaucoma group. Primary open‐angle glaucoma (POAG) (n = 154 eyes), chronic angle‐closure glaucoma (n = 18 eyes), and pseudoexfoliation glaucoma (n = 23 eyes) had odds ratios of 1.90 ( P = .1760), 14.54 ( P = .0006), and 7.27 ( P = .0138), respectively, of refractive surprise greater than ±1.0 D compared with patients without glaucoma. Refractive surprise was noted more often in POAG eyes with axial lengths longer than 25.0 mm ( P = .0298). Glaucoma eyes had worse mean postoperative corrected distance visual acuity than control eyes (glaucoma: 0.1088 logarithm of the minimum angle of resolution [logMAR]; controls: 0.0358 logMAR; P = .01). Conclusion: : Patients with a diagnosis of glaucoma were more likely to have a refractive surprise and/or worse visual outcome after phacoemulsification cataract surgery.